Elevated ergosterol protects Leishmania parasites against antimony‐generated stress. Issue 10 (26th June 2015) - Mathur, Radhika; Das, Rajeev Patrick; Ranjan, Archana; Shaha, Chandrima
ABSTRACT: Parasite lipids can serve as signaling molecules, importantmembrane components, energy suppliers, and pathogenesis factors critical for survival. Functional roles of lipid changes in response to drug‐generated stress in parasite survival remains unclear. To investigate this, Leishmania donovani parasites, the causative agents of kala‐azar, were exposed to the antileishmanial agent potassium antimony tartrate (PAT) (half‐maximal inhibitory concentration ∼ 284 μg/ml). Analysis of cell extracts using gas chromatography‐mass spectrometry showed significant increases in very long‐chain fatty acids (VLCFAs) prior to an increase in ergosterol in PAT‐treated parasites as compared with vehicle‐treated controls. Ergosterol biosynthesis inhibition during PAT treatment decreased cell viability. VLCFA inhibition with specific inhibitors completely abrogated ergosterol upsurge followed by a reduction in cell viability. Following PAT‐induced VLCFA increase, an upsurge in reactive oxygen species (ROS) occurred and inhibition of this ROS with antioxidants abrogated ergosterol increase. Genetically engineered parasites expressing low constitutive ergosterol levels showed more susceptibility to PAT as compared with wild‐type control cells but ergosterol supplementation during PAT treatment increased cell viability. In conclusion, we propose that during antimony treatment, the susceptibility of parasites is determined by the levels of cellular ergosterol that are regulated by oxidative stress generated by VLCFAs.—Mathur, R., Das, R. P., Ranjan, A., Shaha, C. Elevated ergosterol protects Leishmania parasites against antimony‐generated stress. FASEB J. 29, 4201‐4213 (2015). www.fasebj.org